Spritual Education Guidance at The Hasan ‎Ma'shum Dhikr Assembly‎ in Palu - Nursyam; Rahman, Ulfiani; Syamsul Bahri A Galigo; Anirah, Andi; Nadirah, Sitti; Samintang (TADRIS: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to see how far the success of fostering spiritual education in the Hasan Ma'shum Dhikr Assembly‎ in Palu City. The type of this research is field research which is qualitative in nature with a phenomenological approach. The primary data in this study were obtained from information from the leadership, officers, and members of the Hasan Ma'shum Dhikr Council. Meanwhile, secondary data was obtained from documents directly related to the research theme sourced from journals, books, and types of documents sourced from the internet. The data analysis used is qualitative data analysis with an interactive model. The results showed that the process of fostering spiritual education at the Hasan Ma'shum Dhikr Assembly‎ in Palu city consisted of three stages, namely the planning stage which contains socialization planning, preparation of joining, dhikr method, and evaluation. The implementation stage which contains the implementation of the planning stage of socialization, acceptance, dhikr method, and evaluation. The evaluation stage which contains written test, oral test, and non-test. The results of fostering spiritual education at the Hasan Ma'shum Dhikr Assembly‎ in Palu City have been proven to gradually be able to foster their congregations. The success of fostering spiritual education at the Assembly of Dhikr Hasan Ma'shum Palu City consists of a relationship with Allah swt (Hablum minallah) which includes a higher awareness of leaving immoral acts, getting closer to Allah swt, and a feeling of calm and peace in the heart. Meanwhile, human relationships form noble morals and become Uswatun Hasanah.